2022
DOI: 10.1111/1751-2980.13126
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the Paddington International Virtual Electronic ChromoendoScopy ScOre as a good endoscopic score to define mucosal healing and predict long‐term clinical outcomes in ulcerative colitis

Abstract: Objectives To define endoscopic and histological remission in ulcerative colitis (UC) accurately, several scoring systems have been established. A novel virtual electronic chromoendoscopy score, the Paddington International Virtual ChromoendoScopy ScOre (PICaSSO), was developed, validated, and reproduced to assess inflammation grade and predict patient prognosis. We externally verified and validated the clinical value of PICaSSO in UC patients. Methods This prospective study enrolled 63 UC patients. The Mayo e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…57 In the external validation study, a PICaSSO score ≤3 was associated with increased relapsefree survival rates than a score >3 (hazard ratio 0.189). 58 Moreover, the endoscopic remission by VCE-PICaSSO alone has been similar to combined endoscopic and HR for predicting specified clinical outcomes at 12 months in UC patients. 59 Notably, a recent work by Hayashi et al 60 evaluated the usefulness of texture and color enhancement imaging (TXI) (Olympus) in predicting UC relapse.…”
Section: Endoscopic Prediction Of Outcome Through the Eyes Of Enhance...mentioning
confidence: 89%
See 1 more Smart Citation
“…57 In the external validation study, a PICaSSO score ≤3 was associated with increased relapsefree survival rates than a score >3 (hazard ratio 0.189). 58 Moreover, the endoscopic remission by VCE-PICaSSO alone has been similar to combined endoscopic and HR for predicting specified clinical outcomes at 12 months in UC patients. 59 Notably, a recent work by Hayashi et al 60 evaluated the usefulness of texture and color enhancement imaging (TXI) (Olympus) in predicting UC relapse.…”
Section: Endoscopic Prediction Of Outcome Through the Eyes Of Enhance...mentioning
confidence: 89%
“…A large prospective real‐life international study evaluating a cohort of 307 UC patients showed that a PICaSSO score ≤3 predicted major adverse outcomes (MAOs) at 6 and 12 months better than a PICaSSO >3 (hazard ratio 0.19 and 0.22, respectively) and similarly to HR 57 . In the external validation study, a PICaSSO score ≤3 was associated with increased relapse‐free survival rates than a score >3 (hazard ratio 0.189) 58 . Moreover, the endoscopic remission by VCE‐PICaSSO alone has been similar to combined endoscopic and HR for predicting specified clinical outcomes at 12 months in UC patients 59 .…”
Section: Endoscopy‐enabled Prediction Of Clinical Outcome and Respons...mentioning
confidence: 99%